PERLINDUNGAN HUKUM TERHADAP PELANGGAN TERKAIT PENERAPAN PERJANJIAN BAKU SEKTOR PELAYANAN PUBLIK. - Sunanto, Rifto; Tondy, Cicilia Julyani; Irhamsah, Irhamsah (LPPM Institut Pendidikan Nusantara Global, 2024)
This study examines aspects of legal protection for customers in the context of the application of standard agreements in the public service sector. In an effort to provide public services, standard agreements are often used as a legal basis, but this can lead to potential inequalities between service providers and customers. The focus of the study includes the analysis of applicable legal provisions to protect the rights of customers in the public service sector standard agreements, with emphasis on the effectiveness of the protection provided. The research method involves a normative legal study approach to explore various regulations relating to customer protection in the public service sector standard agreements. Furthermore, case studies are used to illustrate the implementation of the raw Agreement and its impact on customers. Thus, this study aims to provide a deeper understanding of the effectiveness of legal protection for customers, with the hope that the results can contribute to improving regulations that pay more attention to customer rights, improve welfare, and ensure justice in public services. The result of this study is the application of standard agreements in the public service sector, as stipulated in Law No. 8 of 1999 on Consumer Protection, confirms that consumer protection is the responsibility of all citizens of Indonesia in accordance with national development goals in the Preamble to the 1945 Constitution. In the midst of the drive to achieve high economic profits and fierce competition, some business actors tend to act fraudulently, harming the interests of consumers. Therefore, legal protection in the public service sector for customers is regulated through standard clauses, which are rules and conditions set by business actors, although consumer protection laws have prohibited the use of standard clauses. Ironically, the conditions in the community indicate that standard agreements are still often used by business actors or entrepreneurs.